Evaluation of the Use of Some Benthic Macro-invertebrate Multimetric Indices Associations with Environmental Variables in Ecological Assessment of Some Ethiopian Rivers - Degefe, Gezahegn; Tamire, Girum; Hassen, Seid Mohammed; Haile, Abinet (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
The ecological status of six selected rivers which are found around central Ethiopia and North Shewa Zone and exposed to environmental stresses at varied extent, was studied using biological quality elements (BQE). One thousand one hundred thirty three (1133) individuals of macroinvertebrates, from 22 families and 5 orders of insects, were collected from the rivers. Seven metrics that had low correlation (p>0.05) were selected to calculate the final B-IBI and the result showed that both sites of Akaki, Sebeta and Jemma Rivers had poor water quality whereas Beresa, Chacha and Mojo (upstream site) had relatively better water quality. Canonical Correspondence Analysis (CCA) showed that Tabanidae, Syrphidae, Culicidae, and Canidae was more strongly correlated with temperature but strongly and negatively with pH, Dissolve Oxygen (DO) and Nitrate. The result implied that the change in abundance of these groups of macroinvertebrates could indicate the change in pH, DO and Nitrate. pH and DO were significantly (p < 0.05) and positively correlated with % Ephemeroptera and% Baetidae. On the other hand, DO showed strong but negative correlation % Oligochaeta, % Non-Insect and Hillsenhoff Family Biotic Index which implied that that the change in pH and level of organic pollution can be easily monitored using these metrics. HYDRO Nepal Journal Journal of Water Energy and Environment Issue: 20 Page: 49-54